THE STRATEGIC EFFICACY OF DRONES FOR US GRAND STRATEGY - Okpaleke, Francis N; Okoli, Al Chukwuma (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This paper assesses the role of drones in furthering or undermining US grand strategy. This is against the backdrop of the thinking that contemporary use of drones in the context of post 9/11 era undermine the successive US administration’s strategic objectives as evidenced by the rise of anti-Americanism in Muslim world, proliferation of drones by US near peer competitors, civilian death toll and weakening support for the US in targeted countries. This implies that while drones has played a historical and significant role for the US in power projection and asserting its unilateralism and military hegemony when dealing with rogue states and terrorist groups post 9/11, the political and strategic utility of drone strikes for US grand strategy is not apparent. Thus, this paper posits that though armed drones has played a quintessential role as a key instrument of statecraft for facilitating US offensive strategy in targeted states, the aftermath of drone strikes and its controversial aspects engender inimical outcomes that serve to undermine US strategic objectives. Based on qualitative analysis of secondary data, the paper questions the wisdom and benefits of using and shifting greater reliance towards armed drones, as a pathway for furthering US grand strategy.